2006
DOI: 10.5380/rsa.v7i1.7271
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos De Níveis E Épocas De Desfolhamento Sobre O Rendimento E Os Componentes Do Rendimento De Grãos Da Soja

Abstract: RESUMOO objetivo do trabalho foi de avaliar o efeito de níveis e épocas de desfolhamento sobre o rendimento de grãos e componentes do rendimento da soja, em semeadura direta. O experimento foi conduzido na Estação Experimental Agronômica da UFRGS, na safra 2002/03. O delineamento experimental utilizado foi o de blocos ao acaso com parcelas sub-subdivididas e quatro repetições. Os tratamentos foram desfolhamento em quatro estádios de desenvolvimento (V9 -nono nó, R2 -floração, R5 -início enchimento do grão, R6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 7 publications
0
9
1
1
Order By: Relevance
“…Ribeiro and Costa (2000) also observed drastic reductions in yield with defoliations greater than 67% at all the developmental stages evaluated, and yields were even weaker if defoliations were applied in the reproductive stages of development. Likewise, in similar trials, Fontoura et al (2006) observed that the treatment with 100% defoliation in the R 5 stage led to the lowest grain yield, with reduction of 76% in relation to the control.…”
Section: Grain Yieldmentioning
confidence: 62%
See 1 more Smart Citation
“…Ribeiro and Costa (2000) also observed drastic reductions in yield with defoliations greater than 67% at all the developmental stages evaluated, and yields were even weaker if defoliations were applied in the reproductive stages of development. Likewise, in similar trials, Fontoura et al (2006) observed that the treatment with 100% defoliation in the R 5 stage led to the lowest grain yield, with reduction of 76% in relation to the control.…”
Section: Grain Yieldmentioning
confidence: 62%
“…However, there are some practices suggested in the literature for the purpose of lessening the damages. According to Costa and Daros (2006), reduction in the spacing between plant rows may decrease the effects caused by defoliation. From the results, it is possible to see that the cultivar BRS Favorita ® exhibits sensitivity to defoliation, with alteration in all the traits evaluated, except for plant height.…”
Section: Grain Yieldmentioning
confidence: 99%
“…Peterson et al (1998) verified that defoliation lower than 50%, before flowering, usually does not decrease grain yield, while in the reproductive stages, it has caused higher reductions in the production. Also, Fontoura et al (2006) report that defoliations lower than 67% did not affect the grain yield of the cultivar 'BR 16' , regardless of the stage.…”
Section: Resultsmentioning
confidence: 92%
“…Similarly, Diogo et al (1997), observed a tendency to increase the productivity with defoliation of 33 and 66%, mainly in the V3 stage. Reichert and Costa (2003) assessed that up to 33% defoliation in the vegetative stages resulted in no change in yield, in the same way, and Fontoura et al (2006) found that there was no significant effect of defoliation in vegetative period on the grain yield, but only assessed the stage V9 within the growing season. Similarly, Peluzio et al (2004) demonstrated that defoliation of 33% in all growth stages and up to 66% by the V5 results in no effect on productivity, results similar to those found in this work, where defoliation from V4 to V9 provided increases in productivity culture in relation to the control treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the percentage of defoliation, research has established levels for the control of insect pests, when the defoliation are greater than 30% in the vegetative phase, or 15% in the reproductive ph ase. However, these recommendations are based on work done in the 70-80's decades (Fontoura et al, 2006). In this sense, another key issue for reduction of income is the degree to which defoliation reduces light interception by the canopy (Higley, 1992).…”
Section: Introductionmentioning
confidence: 99%